The peacemakers: envisioning a Pax Americana in the age of empires - Suchak, N (2023)
The Peacemakers is an imperial history of the American peace movement. The American peace movement – a porous group of cosmopolitan, middle-class Americans – lay at the epicentre of both a transimperial web of peace activism and a broader political ecosystem of nineteenth- century liberal reform. Between 1895 and 1906, the United States, much like its European counterparts, was beset with imperial crises; it violently acquired an insular empire and jostled for position with other empires, as the global imperial system grew to its most expansive and fractious. This thesis explores the liberal conception of the American imperial project, unpacking how ideas of peace, civilisation, and internationalism framed the American imperial imaginary. It addresses a tension at the heart of this vision of empire, namely that liberal thinkers, policymakers, and activists justified imperialism’s inherent violence by appealing to progressive notions of a civilising mission, while also positing that peace stood at the apex of Victorian civilisation. To untangle this contradiction, this thesis asks: How did liberal Americans reconcile their peaceful ideals with their imperial ambitions? The peacemakers envisioned a utopian world of peaceful empire, as they sought to remedy the ills of the nineteenth-century international order by devising and lobbying for solutions rooted in emerging ideas of global governance. This story is instructive in explaining how liberalism, as an ideology of rights and political restraint, was used to justify a political formation characterised by violence and the abrogation of the sovereignty of non-white peoples. Furthermore, this thesis elevates the contingency of the American imperial project, illustrating how American imperialism was consistently made and remade by a variety of state and non-state actors, whose motives and means sat outside the norms of Victorian America’s accepted political discourse.